Immunological responses of turbot (Psetta maxima) to nodavirus infection or polyriboinosinic polyribocytidylic acid (pIC) stimulation, using expressed sequence tags (ESTs) analysis and cDNA microarrays - Park, Kyoung; Osborne, Jane A.; Montes, Ariana; Dios, S.; Nerland, Audun H.; Novoa, Beatriz; Figueras Huerta, Antonio; Brown, Laura L.; Johnson, Stewart (Fish & Shellfish Immunology, 2009)
18 páginas, 3 tablas To investigate the immunological responses of turbot to nodavirus infection or pIC stimulation, we constructed cDNA libraries from liver, kidney and gill tissues of nodavirusinfected fish and examined the differential gene expression within turbot kidney in response to nodavirus infection or pIC stimulation using a turbot cDNA microarray. Turbot were experimentally infected with nodavirus and samples of each tissue were collected at selected time points post-infection. Using equal amount of total RNA at each sampling time, we made three tissue-specific cDNA libraries. After sequencing 3230 clones we obtained 3173 (98.2%) high quality sequences from our liver, kidney and gill libraries. Of these 2568 (80.9%) were identified as known genes and 605 (19.1%) as unknown genes. A total of 768 unique genes were identified. The two largest groups resulting from the classification of ESTs according to function were the cell/organism defense genes (71 uni-genes) and apoptosis-related process (23 uni-genes). Using these clones, a 1920 element cDNA microarray was constructed and used to investigate the differential gene expression within turbot in response to experimental nodavirus infection This work was supported by the NRC-CSIC Canadian-Spanish Cooperation Program. A. Montes gratefully acknowledges the Ministerio de Educación y Ciencia, the CSIC (I3P program) for a research fellowship. Peer reviewed